Analisis Kualitas Udara di Kamar Gelap yang Menggunakan Pengolahan Film Secara Manual dan Otomatis - Ary Kurniawati; Dartini Dartini; Asri Indah Aryani (Jurnal Imejing Diagnostik (JImeD), 2016)
Backgroun: Dark room is the room where the film is being processed as the final stage of the radiographic process, beside its function as a place of handling film and film storage. According to the MSDS, chemical liquid used in film processing can affect human health. It’s spill can cause irritation and burns on skin and eyes, irritation and injury to the digestive tract, while its  mist or dried residue can cause irritation of the respiratory tract. Good dark room air circulation is required.Methods: The study was observational study with measurement data retrieval techniques in the darkroom of four hospitals. The collected data then compared to the air quality requirement according Kepmenkes RI No.1204/Menkes/SK/X/2004 and No.1405/Menkes/SK/XI/2002.Result: The results showed that the physical air quality including temperature and humidity in the 1st, 2nd, 3rd and 4th darkroom was higher than the standards. The average air flow in the 1st, 2nd and 3rd  darkroom were up to standards, but there was no airflow in the 4th darkroom. Results of ambient air quality measurements  in the 1st, 2nd, 3rd and 4th including CO, NO2, SO2 and T.VOC did not meet the standards, while the presence of H2S and NH3 were not detected.Conclusion: Total dust levels in the 1st, 3rd and 4th  darkroom did not exceed the maximum concentration in indoor air ( 0.15 mg/m3), while the 2nd darkroom exceed the standard ( 0, 15 mg/m3). Using of air-conditioning and a dehumidifier with periodic maintenance is needed to resolve the discrepancy physical air quality, beside periodic cleaning and indoor air excahnge maintenance to resolve high levels of dust and gas pollutants.